The influence of motivations and other factors on the results of implementing ISO 9001 standards - Carlos del Castillo-Peces; Carmelo Mercado-Idoeta; Miguel Prado-Roman; Cristina del Castillo-Feito (European Research on Management and Business Economics (ERMBE), 2018)
The objective of this paper is to analyze the influence that the internal and external motivations, as well as other factors can suppose for the appearance of the benefits derived from the adherence to the ISO 9001 Standards. For this, it has been made a research centered in The Spanish construction sector. This sector is of great importance at both the global and Spanish level, and ISO 9001 Standard is widespread in it. A questionnaire was sent to 302 companies that are part of this sector, obtaining 126 valid questionnaires, whose data have been treated using a multiple linear regression model. The results of this model indicate that the type of internal or external motivation to implement such a regulation, as well as the seniority in adhering to it, are significant variables for the achievement of the positive results that can be derived from ISO 9001. However, the size of the company is not significant for the appearance of such results.
Keywords: L2; M1; 650; ISO 9001 Standard; Quality Assurance Standards; Quality management; Spanish construction sector